ChemInform Abstract: Design, Synthesis, and Validation of an Effective, Reusable Silicon‐Based Transfer Agent for Room‐Temperature Pd‐Catalyzed Cross‐Coupling Reactions of Aryl and Heteroaryl Chlorides with Readily Available Aryl Lithium Reagents. Issue 31 (14th July 2016) - Martinez‐Solorio, Dionicio; Melillo, Bruno; Sanchez, Luis; Liang, Yong; Lam, Erwin; Houk, K. N.; Smith, Amos B. III
Abstract: In continuation of previously published studies, an improved silicon‐based transfer agent allowing for cross‐coupling reactions using (hetero)aryl chlorides is designed.